2010
DOI: 10.1890/10-0291
|View full text |Cite
|
Sign up to set email alerts
|

Does Pyrogenicity Protect Burning Plants?

Abstract: Abstract. Pyrogenic plants dominate many fire-prone ecosystems. Their prevalence suggests some advantage to their enhanced flammability, but researchers have had difficulty tying pyrogenicity to individual-level advantages. Based on our review, we propose that enhanced flammability in fire-prone ecosystems should protect the belowground organs and nearby propagules of certain individual plants during fires. We base this hypothesis on five points: (1) organs and propagules by which many fire-adapted plants surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 18 publications
0
25
1
Order By: Relevance
“…Flame duration, total burning time and energy release, expressed as FD (MLC, EPI), GPD (EPI2), THR, AEHC (MLC) and GHC, are important parameters in predicting the biological effects of fire (Gagnon et al, 2010) and evaluating the sustainability of a fuel (Tables 2 and 5) (Hachmi et al, 2011). Flame height and HRR are often used as a proxy for fire line intensity (Agee, 1996;Hachmi et al, 2011) and represent important factors for crown fire initiation and propagation.…”
Section: Sampling Time Aprilmentioning
confidence: 99%
“…Flame duration, total burning time and energy release, expressed as FD (MLC, EPI), GPD (EPI2), THR, AEHC (MLC) and GHC, are important parameters in predicting the biological effects of fire (Gagnon et al, 2010) and evaluating the sustainability of a fuel (Tables 2 and 5) (Hachmi et al, 2011). Flame height and HRR are often used as a proxy for fire line intensity (Agee, 1996;Hachmi et al, 2011) and represent important factors for crown fire initiation and propagation.…”
Section: Sampling Time Aprilmentioning
confidence: 99%
“…Such poor predictive power may be the result of failure by these metrics to incorporate elements of soil heating and potential interactions of above‐ and belowground processes on vegetation (Gagnon et al . ). Given that many plant species survive fires belowground (Vesk & Westoby ; Vesk ), fire metrics that include some aspect of soil heating might better predict how fires affect plant populations and communities.…”
Section: Introductionmentioning
confidence: 97%
“…Keeley ; Gagnon et al . and references therein), empirical studies commonly rely on snapshot‐like aboveground fire metrics that can be poor predictors of vegetation response. Such metrics include fire‐line intensity, maximum fire temperature and fire severity (Johnson ; Whelan ; Bond & van Wilgen ; Bond & Keeley ).…”
Section: Introductionmentioning
confidence: 99%
“…As stated by Gagnon et al (2010) survival of plant's belowground and nearby propagules during fire is related of both the flame-front residence time and degree of damage of the aboveground plant's tissues. Moreover, relationships between fire severity and fire extent can also be established to explain habitat loss or landscape changes (Duffy et al, 2007), despite the spatial heterogeneity in fire severity observed following large fires (Bradstock, 2008).…”
Section: Introductionmentioning
confidence: 99%